2012
DOI: 10.1039/c2jm31054f
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic pre-treatment as a means of enhancing the antibacterial activity and stability of ZnO nanoparticles sonochemically coated on cotton fabrics

Abstract: Zinc oxide nanoparticles (ZnO NP's) are known for their excellent antibacterial properties. This paper describes a method for enhancing the stability and the antibacterial activity of ZnO NPs synthesized and embedded sonochemically on cotton fabrics, by pre-treating the fabric surface with cellulase enzyme. The enzymatic pre-treatment resulted in the deposition of smaller sized NPs with improved adhesion. The reduction in particle size brought about better antibacterial performance against several types of bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…5a, b), showing more narrow distribution of the deposited NPs when the active enzyme was used. These observations corroborate our previous findings that the enzymatic activation of cotton surface leads to uniformly dispersed along the fibers NPs [21]. In the current study a similar effect was achieved using a single-step sono-enzymatic process.…”
Section: Simultaneous Sonochemical/enzymatic Coating Of Cotton With Zsupporting
confidence: 81%
See 3 more Smart Citations
“…5a, b), showing more narrow distribution of the deposited NPs when the active enzyme was used. These observations corroborate our previous findings that the enzymatic activation of cotton surface leads to uniformly dispersed along the fibers NPs [21]. In the current study a similar effect was achieved using a single-step sono-enzymatic process.…”
Section: Simultaneous Sonochemical/enzymatic Coating Of Cotton With Zsupporting
confidence: 81%
“…The higher resistance of S. aureus to ZnO NPs in comparison with E. coli is due to the thicker peptidoglycan layer in the cell wall of Gram-positive bacteria, which makes them less susceptible to metal oxide NPs [33,34]. The results also showed that the durability of the antibacterial effect of the ZnO NP coating obtained in the one step sono-enzymatic coating approach against E. coli was higher compared to the already reported durability of the coating obtained in the two stepprocess (consisting of enzymatic pre-treatment of the cotton textiles followed by sonochemical deposition of ZnO NPs) [21].…”
Section: 3antibacterial Activitymentioning
confidence: 45%
See 2 more Smart Citations
“…Therefore, considerable efforts have been made to make a uniform size distribution using advanced technologies. Recent studies have shown that their small sizes have more antibacterial properties than larger particles (Perelshtein et al, 2012).…”
Section: Introductionmentioning
confidence: 99%